Diffuse Alveolar Hemorrhage Synergistically Induced by Amiodarone and Rheumatoid Arthritis - Ahmad Assad MD; Mohammad Alkhaldi MD; Andrew Abrahamian MD; Brandon Yonel MD; Ragheb Assaly MD; Nazem Altorok MD (SAGE Publishing, 2023)
Diffuse alveolar hemorrhage (DAH) syndrome is characterized by bleeding into the alveolar spaces of the lungs and occurs when there is an injury to the alveolar microcirculation that leads to hemorrhage from the alveolar capillaries. We report a case of an 82-year-old woman who presented with acute respiratory distress. The patient had a history of rheumatoid arthritis (RA) and was on amiodarone for atrial fibrillation therapy. Initial diagnostic workup, including bronchoscopy and imaging studies, revealed diffuse opacities and the bronchoalveolar lavage fluid consistent with DAH. The patient required aggressive management with supportive care and corticosteroids. Laboratory work showed a synergistic effect between amiodarone and RA in inducing DAH. This makes the report unique as no reports in the literature described a synergic effect of amiodarone and RA in inducing DAH. The primary objective of this report is to guide physicians and remind them to keep DAH at the top of their differential diagnosis in the setting of an RA patient taking amiodarone.